Diálogos com Padre Brown: círculos, romances e modus operandi de G. K. Chesterton - Martins, Glauber Ormundo Dias (2024)
This thesis is situated within the field of studies concerning the relationships between the social sciences and literary production. Its primary focus is on the trajectory of the English author G. K. Chesterton, in dialogue with the detective stories of The Innocence of Father Brown. The research problem is centred on the hypothesis that Chesterton's intellectual production is intricately connected to the polemical intellectual circles of 19th-century England. The investigation seeks to determine whether the author's detective novels establish connections and analogies with his other works in literature, philosophy, politics, and theology, and if it is feasible to engage in a dialogue between the novels and the author's critical modus operandi. The objective of this work is to identify correlations between Chesterton's detective novels, particularly The Innocence of Father Brown, and to establish dialogues with the intellectual circles (Williams, 2005) in which the author participated; with the European culture of the 19th century (Lepenies, 1996); with the history of Don Quixote, based on Borges' analysis (2011) suggesting that the book extends the author's memory; and with Chesterton's critical perspectives presented in writings beyond detective novels. The methodological protocol for the research is anchored in several axes: a bibliographic survey, theoretical-conceptual profiling specifically associated with the detective novel genre, Chesterton's relationship with the genre, his philosophical views, the dialogue of these views with other social science authors, and engagement with the criticism of his work during that period. Through an integration of authors from the fields of Anthropology, Sociology of Culture, Literature, and Literary Criticism, the work is fundamentally centred on the concepts of "circle" and "structure of feelings" (Williams, 1992, 1979) and the correlation between Chesterton's position in the intellectual field of 19th-century England and his literary, philosophical, political, and theological production. The theoretical framework primarily relies on authors such as Williams (1979, 1992, 2005, 2011), Bakhtin (1997), Borges (2011), and Weber (1974, 1997, 2003)